Water management control system of IoT-based solar irrigation system - Tan, Zhen Kang (2021)
In the present era, demand of food is increasing due to increasement of population of people in the world. However, our supply of foods does not meet the demand of food for the people all the around the world. For example, Africa is currently facing the food crisis since 1945. Collision of climate change and population growth has created massive food shortages in Africa, and this would cause millions of dies in coming months. Plant is the main source of food providing us with fruits and vegetables, which are an important source of fibres, proteins, and carbohydrates. But the ways of plantation in our world still not optimise to a high production to produce enough demand for the market. Therefore, to overcome this problem, an automated irrigation system is vital in current situation. Automated irrigation system not only can reduce the amount of manpower but also make the plantation to be more systematic and easier to manage. Just at your fingertips, the irrigation can be control and monitor though the smart device. The aim of this solar irrigation system is to provide a technology of automated irrigation system to the farmer or industry. This technology could be operated in anywhere even there is no supply of electricity as long as there is existing of sunlight. Besides, this system is completed with sensors which could immediately give a notification to the user through application. The objective of our project is mainly about designing of IoT-based solar irrigation system. Therefore, in this thesis, the whole system is developed with assistant of solar power. The system includes the microcontrollers, sensors, solenoid valve and LCD. The present of microcomputer is to control the water flow and give information to the user through device on irrigation system. Solenoid valve is the component which control by the microcomputer meanwhile the sensor is to collect the information of real situation environment. In result, we success to develop a system which able to irrigate the crops or plants using solenoid valve controlled by smartphone with monitoring features. These monitoring features are able to view either in mobile application or browser in any devices and controlling function of valve is able to use through the mobile application. This system is completed with water management features which the information of water pressure, flow rate and total amount of water display on the LCD.